Use of the resilience concept in the CEFR-aligned english for science and technology (EST) classes in malaysian secondary schools through victorian literature - Rahman A.Z.A.; Chong S.T.; Kaman Z.K.; Leon C.E. (Institute of Electrical and Electronics Engineers Inc., 2023)
Floods; Students; English languages; Flood disaster; Literary texts; National level; Science and Technology; Secondary schools; Smooth transitions; Work in progress; Social sciences computing